3D Printing of Core–Shell Capsule Composites for Post‐Reactive and Damage Sensing Applications. Issue 11 (21st September 2020) - Rupp, Harald; Binder, Wolfgang H.
Abstract: 3D printing of multicomponent materials as an advantageous method over traditional mold casting methods is demonstrated, developing small core–shell capsule composites fabricated by a two‐step 3D printing process. Using a two‐print‐head system (fused deposition modeling extruder and a liquid inkjet print head), micro‐sized capsules are manufactured in sizes ranging from 100 to 800 µm. The thermoplastic polymer poly(ε‐caprolactone) (PCL) is chosen as matrix/shell material due to its optimal interaction with the embedded hydrophobic liquids. First, the core–shell capsules are printed with model liquids and pure PCL to optimize the printing parameters and to ensure fully enclosed capsules inside the polymer. As a proof of concept, novel "click" reaction systems, used in self‐healing and stress‐detection applications, are manufactured in which PCL composites with nano‐ and micro‐fillers are combined with reactive, encapsulated liquids. The so generated 3D printed core–shell capsule composite can be used for post‐printing reactions and damage sensing when combined with a fluorogenic dye. Abstract : Herein, a 3D printing process using a dual‐dispensing system, allowing the printing of liquid‐filled capsules (100–800 µm) inside a thermoplastic polymer matrix, is reported. A multi‐compartment system is developed based on model‐liquids and PCL to optimize the printing parameters. With the post‐printed concept reactive PCl‐composites with nano‐ and micro‐fillers are manufactured, combined with encapsulated liquids.